2011
DOI: 10.1007/s10439-011-0455-6
|View full text |Cite
|
Sign up to set email alerts
|

Organs-on-a-Chip: A Focus on Compartmentalized Microdevices

Abstract: Advances in microengineering technologies have enabled a variety of insights into biomedical sciences that would not have been possible with conventional techniques. Engineering microenvironments that simulate in vivo organ systems may provide critical insight into the cellular basis for pathophysiologies, development, and homeostasis in various organs, while curtailing the high experimental costs and complexities associated with in vivo studies. In this article, we aim to survey recent attempts to extend tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
141
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 107 publications
0
141
0
Order By: Relevance
“…To this end, the recently emerged organ-on-a-chip systems that combine advanced microfluidic technologies and tissue engineering approaches to simulate both the biology and physiology of human organs have been developed (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the recently emerged organ-on-a-chip systems that combine advanced microfluidic technologies and tissue engineering approaches to simulate both the biology and physiology of human organs have been developed (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31).…”
Section: Significancementioning
confidence: 99%
“…These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31). Although a majority of focus in the field has been placed on the construction of biomimetic organ models (7,15,(31)(32)(33), it is increasingly recognized that incorporating biosensing would allow for in situ monitoring of the status of these miniaturized organs (9,34). Such a need originates from the fact that many drugs can trigger chronic cellular reactions, whereas others may induce delayed cell responses.…”
Section: Significancementioning
confidence: 99%
“…Knowledge of these interactions will significantly improve our understanding of the nature of the human body at the tissue and cellular levels. (1) In addition, the development of new drugs and disease therapies will benefit if the interaction between specific cells and drugs can be screened directly. (2) In the longer term, the goal is to directly and precisely mimic the in vivo microenvironments and to understand their internal interactions with drugs.…”
Section: Introductionmentioning
confidence: 99%
“…(1,12) Such devices include the biological functions of organs and the biochemical, bioelectrical, and biomechanical properties of cellular microenvironments and extracellular matrixes (ECMs). Recent studies have demonstrated the feasibility of organ-on-a-chip systems, which can closely mimic in vivo tissues and provide platforms for drug delivery test and biological cell characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation